Design and synthesis of eugenol/isoeugenol glycoconjugates and other analogues as antifungal agents against Aspergillus fumigatus - Goswami, Lakshmi; Gupta, Lovely; Paul, Sayantan; Vermani, Maansi; Vijayaraghavan, Pooja; Bhattacharya, Asish K. (RSC Medicinal Chemistry, 2022)
Glycoconjugates are biologically significant molecules as they tend to serve a wide range of intra- and extra-cellular processes depending on their size and complexity. The secondary metabolites of the plant Myristica fragrans, eugenol and isoeugenol, have shown antifungal activities (IC50 1900 mu M). Therefore, we envisioned that glycoconjugates based on these two scaffolds could prove to be potent antifungal agents. Triazole-containing compounds have shown prominent activities as antifungal agents. Based on this, we opined that a Cu(i) catalyzed click reaction could serve as the bridging tool between a eugenol/isoeugenol moiety and sugars to synthesize eugenol/isoeugenol based glycoconjugates. In our present work, we have coupled propargylated eugenol/isoeugenol and azido sugar to furnish eugenol/isoeugenol based glycoconjugates. In another approach, we have carried out hydroxylation of the double bond of eugenol and subsequent azidation of a primary alcohol followed by intramolecular coupling reactions leading to various other analogues. All the synthesized compounds were assayed against an opportunistic pathogenic fungus, Aspergillus fumigatus. Among the synthesized compounds, two analogues have exhibited significant antifungal activities with IC50 values of 5.42 and 9.39 mu M, respectively. The study suggested that these two analogues inhibit cell wall-associated melanin hydrophobicity along with the number of conidia. The synthesized compounds were found to be non-cytotoxic to an untransformed cell line.